The Implementation of the "PAK DALANG KEPASAR" Program (On-Site Population Administration Services for Vulnerable Communities) by the Gresik Regency Population and Civil Registry Office - Umi Sholihatu Marfu’atin; Rahma Sari; Diva Citra Irdyanti; Noor Abika Diva Ainura; Binti Azizatun Nafi’ah (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Population administration is a key foundation of inclusive and equitable governance. However, vulnerable groups such as the elderly, persons with disabilities, individuals with mental disorders, and chronically poor citizens often face obstacles in accessing services. To address this issue, the Department of Population and Civil Registration of Gresik launched the "Pak Dalang Kepasar" program, a mobile administrative service targeting vulnerable populations. This study analyzes the implementation of the program using Van Meter and Van Horn’s policy implementation model, which includes six variables. The research applies a qualitative approach using interviews, observation, and documentation. Findings show that the program has clear objectives, measurable service targets, and a regular evaluation system. Human resources and equipment are relatively adequate, though some technical limitations persist in the field. Implementers exhibit a positive and inclusive attitude and successfully coordinate with village officials. Supportive social environments and economic challenges among citizens reinforce the urgency of this program. As of the study period, more than 200 vulnerable residents had received services. Overall, the program successfully reaches groups previously excluded from administrative services while promoting a more humane and responsive approach to vulnerable communities.